2014
DOI: 10.7589/2013-08-194
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydiaceae and Chlamydia-Like Organisms in Free-Living Small Mammals in Europe and Afghanistan

Abstract: ABSTRACT:Few data are available on the occurrence of chlamydial infections in wild small mammals. We investigated the significance of free-living small mammals as reservoirs or transmission hosts for microorganisms of the phylum/class Chlamydiae. We obtained 3,664 tissue samples from 911 animals in Switzerland, Germany, Austria, the Czech Republic, and Afghanistan. Samples included internal organs (n53,652) and feces (n512) from 679 rodents (order Rodentia) and 232 insectivores (order Soricomorpha) and were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
6
1
1
Order By: Relevance
“…Samples were considered positive if duplicate samples had a Ct value of <40. Positive samples were confirmed by a follow-up qPCR detecting the secY gene [22] , coding for a preprotein translocase membrane subunit. All 48 samples were negative for both Waddlia and Parachlamydiaceae.…”
mentioning
confidence: 99%
“…Samples were considered positive if duplicate samples had a Ct value of <40. Positive samples were confirmed by a follow-up qPCR detecting the secY gene [22] , coding for a preprotein translocase membrane subunit. All 48 samples were negative for both Waddlia and Parachlamydiaceae.…”
mentioning
confidence: 99%
“…To our knowledge, only one other attempt to detect or isolate chlamydiae from non-domesticated small mammal sources has been reported. Stephan et al (2014) reported using nucleic acid detection methodologies to detect chlamydial infection in European shrews and reported only rare positives, indicating very low endemicity of chlamydial infection (Stephan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, only one wild rodent out of 746 was positive by PCR [12], showing the low prevalence of this bacteria in this setting Fig. 2. 3.…”
Section: Q1mentioning
confidence: 93%